Adhesive wear resistance of Cu-Sn-Zn-Pb bronze with additions of Fe, Mn and P - Turhan, H (Elsevier Science Bv, 2005)
In this work. the effects of Fe, Mn and P elements on the wear resistance of Cu-Sn-Zn-Pb bronzes have been experimental investigated. For this aim, the test specimens have been produced as cast bronze alloys and whom Fe, Mn and P elements were added immediately. The produced samples have then been submitted to adhesive wear resistance tests. The wear resistance of specimens have been determined as a function between weight loss and sliding distance. The samples containing P elements showed the best abrasive wear resistance. But Fe and Mn elements reduced wear resistance of bronzes because of the existence of intermetallic compounds. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Cu-Sn-Zn-Pb bronzes; wear behaviour; adhesive wear; X-ray diffraction analyses